Paraoxonase-1 activity and oxidative status in patients with knee osteoarthritis and their relationship with radiological and clinical parameters - SELEK, ŞAHABETTİN; Erturk, Cemil; KOÇYİĞİT, ABDÜRRAHİM; Altay, Mehmet Akif; Selek, Sahbettin; Kocyigit, ABDÜRRAHİM (My University, 2012)
Background. The aim of this study was to investigate serum paraoxonase-1 (PON1) activity and oxidative/anti-oxidative status in knee osteoarthritis (OA), and evaluate their relationship using radiological and clinical parameters. Materials and methods. The study population comprised 127 patients with knee OA and 107 healthy volunteers. Patients with knee OA were divided into four subgroups according to the Kellgren-Lawrence (K&L) grading scale. In addition, each patient was clinically evaluated by the Western Ontario and McMaster University Osteoarthritis Index (WOMAC). Serum PON1 activity was measured spectrophotometrically. Oxidative status was assessed by measuring serum lipid hydroperoxide (LOOH) and total oxidant status (TOS). Anti-oxidative status was assessed by measuring serum free sulfydryl groups (-SH = total thiol) and total antioxidant capacity (TAC). Oxidative stress index (OSI) was calculated. Lipid parameters were determined by routine laboratory methods. Results. Serum PON1 activity was significantly lower in the knee OA group compared to the control group (p 0.05). The lowest and highest mean serum PON1 activities were detected in patients with grades 4 and 1, respectively (ANOVA p < 0.001). In multiple regression analysis, WOMAC score was independently associated with serum PON1 activity (beta = -0.248, p = 0.027). Conclusions. Decreased serum PON1 activity and elevated LOOH, TOS, and OSI levels may be associated with knee OA, and serum PON1 activity may be a useful adjunctive indicator of the severity of knee OA for follow-up.